Stylistic Simile in the Poetry of Ebn Al-Mutaz - Khairia Agrash ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The simile  is a high status according to Ibn Al-Mutaz. In this article, we have studied the simile in his poetry, a stylistic study, in order to know its artistic andstylistic value and on the features that dominate its similes to be taken into consideration.We presented this similarity when we talked about it, its importance, and how it is used in his poetry and we saw that the poet relied on it to show his ingenuity.Ibn Al-Mu'taz applied poetic and expressive images in a brilliant literary application as if he was drawing nature when describing it, his description abounds in beautiful paintings, and the basis of his description is simile.